'Stuck in the quagmire of an HIV ghetto': the meaning of stigma in the lives of older black gay and bisexual men living with HIV in New York City. - Haile, Rahwa; Padilla, Mark B; Parker, Edith A (Culture, health & sexuality, 2011)
In this paper, we analyse the life history narratives of 10 poor gay and bisexual Black men over the age of 50 living with HIV/AIDS in New York City, focusing on experiences of stigma. Three overarching themes are identified. First, participants described the ways in which stigma marks them as 'just one more body' within social and medical institutions, emphasising the dehumanisation they experience in these settings. Second, respondents described the process of 'knowing your place' within social hierarchies as a means through which they are rendered tolerable. Finally, interviewees described the dynamics of stigma as all-consuming, relegating them to the 'quagmire of an HIV ghetto'. These findings emphasise that despite advances in treatment and an aging population of persons living with HIV, entrenched social stigmas continue to endanger the well-being of Black men who have sex with men.
Keywords: Adaptation, Psychological; African Americans; Age Factors; Aging; Bisexuality; Culture; Health Status Disparities; HIV Infections; Homosexuality, Male; Humans; Male; Mental Health; Middle Aged; New York City; Poverty Areas; Prejudice; Qualitative Research; Social Class; Stress, Psychological; Tape Recording; United States